METODE PENELITIAN KUALITATIF DAN RAGAMNYA: Qualitative Research Methods And Their Varieties - Faisal Abdullah Faisal Abdullah (Al-Thifl: Jurnal Pendidikan Anak Usia Dini, 2024)
The purpose of this article is to understand the design of qualitative research methods. The method used is library research, collecting data by searching for sources and constructing them from various sources such as books, journals and existing research. The result is that qualitative research methods are research that deals with non-numerical data, by analyzing and interpreting texts and interview results with the aim of finding the meaning of a phenomenon in a holistic-contextual manner by collecting data from natural settings and using the researcher as a key instrument. Qualitative research has a descriptive nature and tends to use an inductive approach to analysis, so that processes and meanings based on the subject's perspective are more emphasized in this qualitative research. This qualitative research can be used as a method in research, because the design is explained comprehensively and is easy for researchers and academics to understand.